(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدفت الدراسة إلى تعرّف مستوى اكتساب تلاميذ الصف الرابع الأساسي لمهارات عمليات العلم المتمثلة بالملاحظة والتصنيف والتنبؤ، وأثر الجنس والتحصيل الدراسي على هذا الاكتساب، وعلاقته مع التفكير الناقد. ولتحقيق ذلك، استخدم المنهج الوصفي التحليلي، وأعدّ مقياساً لمهارات عمليات العلم وآخر للتفكير الناقد، حيث تم التأكد من صدقهما وثباتهما، ووزعا على عينة قوامها (137) تلميذاً وتلميذة من تلاميذ الصف الرابع الأساسي في محافظة اللاذقية. وأظهرت النتائج أنّ عينة البحث تمتلك مهارات عمليات العلم المدروسة بمستوى ضعيف؛ أقل من المستوى الفرضي (50%)، وإناث الصف الرابع يمتلكن مهارات عمليات العلم بدرجة أكبر مما يمتلكها الذكور، والتلاميذ مرتفعي التحصيل يمتلكونها بدرجة أكبر مما يمتلكها التلاميذ منخفضو التحصيل، وتبين وجود علاقة ارتباطية موجبة بين مهارات عمليات العلم والتفكير الناقد. واقترح القيام بتدريس مهارات عمليات العلم لتنمية مهارات التفكير المعرفية وما وراء المعرفة. The purpose of this study is to examine the level of acquiring science process skills (observation, classification, prediction) by fourth graders and to investigate the effect of gender and achievement, identifying their relationship with critical thinking. To that end, the researchers use the analytical descriptive method, preparing reliable, valid scales to measure science process skills and critical thinking. The sample used consists of (137) students in Lattakia. The results show that students poorly perform science process skills (observation, classification, prediction). Females’ scores on the scale of science process skills are better than males’ scores; high achievement students’ scores on the same scale are better than low achievement ones. There is a positive correlative relationship between science process skills and critical thinking. The researchers suggest teaching science process skills for developing cognitive and meta-cognitive thinking skills.